Fluctuation solution theory of pure fluids - Ploetz, Elizabeth A.; Pallewela, Gayani N.; Smith, Paul E. (My University, 2017)
Fluctuation Solution Theory (FST) provides an alternative view of fluid thermodynamics in terms of pair fluctuations in the particle number and excess energy observed for an equivalent open system. Here we extend the FST approach to provide a series of triplet and quadruplet particle and excess energy fluctuations that can also be used to help understand the behavior of fluids. The fluctuations for the gas, liquid, and supercritical regions of three fluids (H2O, CO2, and SF6) are then determined from accurate equations of state. Many of the fluctuating quantities change sign on moving from the gas to liquid phase and, therefore, we argue that the fluctuations can be used to characterize gas and liquid behavior. Further analysis provides an approach to isolate contributions to the excess energy fluctuations arising from just the intermolecular interactions and also indicates that the triplet and quadruplet particle fluctuations are related to the pair particle fluctuations by a simple power law for large regions of the phase diagram away from the critical point. Published by AIP Publishing.
Citation: Ploetz, E. A., Pallewela, G. N., & Smith, P. E. (2017). Fluctuation solution theory of pure fluids. Journal of Chemical Physics, 146(9), 13. doi:10.1063/1.4977040
Keywords: Partial Molar Properties; Thermodynamic Properties; Computer; Calculation; Water; Formulation